Congressional bribery as state-corporate crime: a social network analysis - Peoples, Clayton D. (Crime, law and social change, 2015)
There have been a number of high-profile cases of Congressional bribery over the years. This was especially true in the 109th House (2005-06), during which ranking members such as Tom DeLay, Bob Ney, and "Duke" Cunningham were indicted. Some members of Congress argue that these were just a "few bad apples," but the public believes that Congress is more widely corrupt. We employ social network analysis to test which view is correct. We analyze comprehensive data on all members of the 109th House, including their roll call voting and receipts of Political Action Committee (PAC) contributions. Our results show that PAC donors had a significant influence on lawmaker voting across party - despite the fact that such influence is illegal under the Federal Bribery Statute. Accordingly, we find strong support for institutional corruption within Congress. Our findings challenge the traditional conceptualization of political bribery as an individual form of occupational crime, and we argue that it should instead be viewed as a state-corporate crime in its own right. We argue further that it can act as a facilitative process that enables other forms of state-corporate offending to occur, thereby causing social harm. The unique ability of social network analysis to treat relationships as a unit of analysis is central in these findings and conclusions. Hence, we contribute to the emerging trend of applying social network analysis in criminology by providing a new application to state-corporate offending.